Anti-Salmonella activity of plant species in the Benin republic: Artemisia afra and Detarium senegalense with promising in vitro and in vivo activities - LAGNIKA, LATIFOU (My University, 2023)
Non-typhoidal invasive Salmonella (NTiS) diseases are one of the most important zoonoses in the world. This study explored the antipathogenic potential of twenty-four plants used in Benin folk medicine against NTiS diseases. The in vitro antibacterial and antibiofilm activities of ethanolic plant extracts were screened against clinical resistant isolates and ATCC reference strains of Salmonella. Salmonella enterica serovar Typhimuriuminfected rat model was used to examine the in vivo antibacterial potential of plant extracts. Of the 24 plants, 18 plants exhibited antibacterial activity against Salmonella enterica strains with minimum inhibitory concentrations (MICs) ranging from 0.156 to 1.25 mg/mL. Anacardium occidentale, Artemisia afra, Detarium microcarpum, Detarium senegalense, and Leucaena leucocephala were the most active plant species. Extracts from A. afra, D. microcarpum, and D. senegalense showed biofilm inhibition greater than 50% against Salmonella clinical isolates. In the rat model of infection, A. afra and D. senegalense extracts were found to have an effective dose of less than 100 mg/kg and to stop the salmonellosis after 10 days of treatment. Additionally, these extracts did not produce any toxic effects in the treated animals. These results indicate clear evidence supporting the anti-Salmonella activity of A. afra and D. senegalense. Further studies are now needed to isolate bioactive compounds and to ensure the safety of these plant species.
Keywords: Zoonotic diseases; Salmonellosis; MIC; Antibiofilm; Medicinal plants; Ethnobotany